Pengelolaan Guru Pendidikan Agama dalam Konteks Desentralisasi Pendidikan - Hayadin -- (Jurnal Pendidikan dan Kebudayaan, 2012)
The objective of this study is to describe the process of managing religious education teachers in the era of decentralization of education in Palangkaraya City, Central Kalimantan Province. This study was a case study–qualitative in nature which was conducted in 2010. The data was collected directly in Palangkaraya City using primary and secondary data sources, which is information and document from office of the Ministry of Religious Affairs, education office, and local personnel board of Palangkaraya City. To collect the data, the researcher used interview and document study with interview sheets and checklist. The data was verified through triangulation to some resource persons in relation to the one research problem in order to ensure the validity and reliability. The findings showed that: 1) recruitment of religious education teachers was also conducted by Palangkaraya local administration in order to meet the requirement of religious teachers in the city because the number of teachers appointed by the central government (cq, Ministry of Religious Affairs) is so small; 2) In the process of career development and welfare, religious education teacher is treated with the same respect as other teachers; 3) Socialpolitical conditions and the clarity of Regional Personnel Board Regulation concerning management of local personnel are other factors contributing to the management of religious education teachers in Palangkaraya City.